Assessing the scientific basis and regional applicability of a Chinese agrometeorological proverb in a warming climate - Chen, Shuo; Huang, Yonghan; Shao, Congying; Shen, Baoguo; Shuai, Yanmin (Frontiers in Environmental Science, 2025)
Chinese Agrometeorological Proverbs represent a valuable repository of traditional knowledge supporting agricultural practices; however, their scientific validity and regional applicability under climate change remain insufficiently examined. This study evaluates the proverb “The heat of Dog Days on double Beginning of Spring of the Lunar Years” using daily meteorological data from 699 stations across China (1966–2019). We compared temperature trends between Double-Beginning of Spring Lunar Years (BSLY) and Normal Years (NY) from the Beginning of Spring to Minor Heat to identify periods of “Rapid Warming” (RW), and assessed the intensity of “Dog Days Heat” (DDH) using the Temperature-Humidity Index (THI). The results reveal spatially varying consistency with the RW characteristic: southern China and the middle-lower Yellow River basin showed the strongest agreement, meeting the RW criterion within both 31 and 46 days after the Beginning of Spring. During the Dog Days period, BSLY exhibited significantly higher heat intensity in southern regions, with spatial variations influenced by topography and local climate conditions. This research confirms the scientific basis of the proverb and demonstrates that its applicability extends beyond its region of origin. The findings provide practical insights for integrating traditional knowledge into climate-resilient agricultural planning, supporting adaptive strategies under changing climatic conditions.